Teleoperated mobile robot with two arms: the influence of a human-machine interface, VR training and operator age. Issue 156 (December 2021) - Grabowski, Andrzej; Jankowski, Jarosław; Wodzyński, Mieszko
Highlights: Novel results of extensive study with 81 subjects showing the influence of type of human-machine interface, VR training and age of the operator on remote controlling of a mobile robot with two arms are presented The human-machine interface using Head Worn Display for telepresence is presented The construction of the teleoperated robot with two arms is described The operator's work effectiveness was examined The subjective indicators such as usability, acceptance of technology, or the operator's fatigue and stress level are investigated The results show that the age is more important factor than type of human-machine interface or virtual training The VR training is not beneficial for relatively simply task performed using teleoperated robot Abstract: The article presents a method of supporting work by using virtual reality techniques to control a two-armed mobile robot's movement. The robot developed for the study can carry a 20 kg load (10 kg in each arm), and its price is low enough to enable mass implementation in industry (e.g., in warehouses). The results of a study conducted with 81 participants (63 young and 18 older active workers), divided into five study groups, are discussed. Three main factors are considered: human-machine interface, training in virtual reality and operator's age. The operator's work effectiveness was examined. Subjective indicators, such as usability, acceptance of technology, or the operator's fatigue and stress level were also investigated. Our results indicate, among others, that interface without walking is considered the most useful, short VR training does not increase the operator's efficiency, and older operators are much less willing to accept this kind of technology. The robot's description and how it is controlled are presented in the paper.